Leishmaniose visceral: implicações epidemiológicas da ausência do diagnóstico sorológico e do recolhimento de cães sororreagentes em Belo Horizonte - Livia Andrade Alves (2015)
Visceral leishmaniasis has significantly increased its importance in the context of public health in Brazil. This study aimed to evaluate the epidemiological implications of lack of diagnosis and gathering of seropositive dogs in the Sanitary District (DS) east of Belo Horizonte, Minas Gerais. We conducted an observational, descriptive and analytical study on visceral leishmaniasis in that health district. The average prevalence of canine visceral leishmaniasis (CVL) in DS East in the period from 2011 to 2013, was 2.8% with a collection rate of 16 seropositive dogs of 92%. The average absence of diagnosis in 14 areas of regional coverage was 37% (15% - 56%) in 2012 and 31% (18% - 38%) in 2013. The relationship between the lack of diagnosis with Index Vulnerability Health showed that in low-risk areas there is greater risk of dogs not being examined compared to areas of medium, high and very high risk. A risk 1.3-fold was found (p <0.05) for the occurrence of cases of human visceral leishmaniasis (LVH) in the presence of the positive dog. As for the occurrence of LVC found risk of 1.043 (p <0.05) with no diagnosis and a risk of 1.047 (p <0.05) with the nonpayment of seropositive dogs. It was also found that the animals not collected in the years 2011 to 2013 an average of 33.1% were being treated for LVC according veterinary clinical reports, the others are refusals, vaccinated and house closed. Thus, the results suggest that monitoring the number of diagnostic absences by consolidating these data and the non-payment of seropositive dogs is needed to better effectiveness of the control program of visceral leishmaniasis.